THE CORRELATION BETWEEN READING HABIT AND READING COMPREHENSION OF THE FOURTH SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM FKIP UNIVERSITAS RIAU - Yusnaeni, Rahma; Masyhur, Masyhur; Syarfi, M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was aimed at finding out the correlation between reading habit and reading comprehension of the fourth semester students of English Study Program FKIP Universitas Riau. The researcher implemented a quantitative correlational research design. The number of sample are 37 students chosen by using cluster random sampling. There were two data obtained in this research: students’ reading habit and their reading comprehension. The questionnaire was used to score students’ reading habit while reading test was used to score their reading comprehension. The results show that the r-obtained is 0.514 with the significant level 0,001 which means that there is a significant correlation between reading habit and reading comprehension. The value of R square shows that the relationship between reading habit and reading comprehension of the students is 26.4%. In other words, it is implied that the higher students’ reading habit, the higher reading comprehension score they might get.Key Words: Correlation, Reading Habit, Reading Comprehension